Stuff : The life of a cool demented dude - Strong, Jeremy; Armstrong, Matthew, illus (London : Puffin, 2005)
Fourteen-year-old Simon, known as Stuff, struggles with his new stepfamily, tries to avoid a giant attack rabbit, hopes to break up with his girlfriend and connect with a new one, and creates cartoons of "Punykid's battle with drooling dorkoids.".
Keywords: cartoons and comics -- Fiction; School -- Fiction; Stepfamilies -- Fiction